Diurnal variation in choroidal thickness in relation to sex, axial length, and baseline choroidal thickness in healthy Korean subjects - Lee, Seung Won; Yu, Seung-Young; Seo, Kyung Hoon; Kim, Eung Suk; Kwak, Hyung Woo (Retina (Philadelphia, Pa.), 2014)
To investigate diurnal variations in choroidal thickness (CT) in relation to various factors in healthy Korean subjects using spectral-domain optical coherence tomography. A prospective study was conducted on 100 healthy volunteers who each underwent measurements of CT in the same subfoveal area using an enhanced depth imaging technique with spectral-domain optical coherence tomography at 8 AM, 11 AM, 2 PM, and 5 PM. Possible correlations between the diurnal variation of CT and other factors, such as sex, axial length (AL), baseline CT (8 AM), blood pressure, and intraocular pressure, were evaluated. One hundred volunteers with a mean age of 30.1 years were scanned. A significant pattern of diurnal variation was observed, with a mean CT of 278.28 ± 91.78 μm at 8 AM, 271.57 ± 89.08 μm at 11 AM, 266.39 ± 86.18 μm at 2 PM, and 264.92 ± 87.10 μm at 5 PM in a right eye. Right eye and left eye had a similar trend of diurnal cycle. Based on sex, AL, and baseline CT, the pattern of diurnal variation was greater and the amplitude significantly was greater in men, AL ≤ 24 mm and baseline CT ≥ 300 μm (men vs. women: P = 0.048, AL ≤ 24 mm vs. AL > 24 mm: P = 0.036, baseline CT ≥ 300 μm vs. baseline CT < 200 μm: P = 0.002, baseline CT ≥ 300 μm vs. 200 μm ≤ baseline CT < 300 μm: P = 0.008). There were no significant correlations between the diurnal variation of CT and systolic blood pressure, diastolic blood pressure, or intraocular pressure. In men as well as in those with a shorter AL and thick baseline CT, a greater pattern of diurnal variation with significantly greater amplitude was observed.